2008
DOI: 10.1007/s11695-008-9509-8
|View full text |Cite
|
Sign up to set email alerts
|

BioEnterics Intragastric Balloon for Treatment of Morbid Obesity in Prader–Willi Syndrome: Specific Risks and Benefits

Abstract: This study shows that when noninvasive pharmacological therapies fail, BIB may be effective to control body weight in PWS patients with morbid obesity, particularly when treatment is started in early childhood. However, careful clinical follow-up and close collaboration with parents are crucial to avoid severe complications, which can be caused by persisting unrestrained food intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…Therefore, intragastric balloon therapy is regarded to be more appropriate for patients with relatively mild obesity. Previous reports showed that 2 consecutive balloon therapies (6) and repeated balloon therapies (7) achieved good results after 12 months of treatment, and multiple balloon therapies were effective maintenance treatment to control body weight in Prader-Willi syndrome patients when treatment was started in early childhood (8).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, intragastric balloon therapy is regarded to be more appropriate for patients with relatively mild obesity. Previous reports showed that 2 consecutive balloon therapies (6) and repeated balloon therapies (7) achieved good results after 12 months of treatment, and multiple balloon therapies were effective maintenance treatment to control body weight in Prader-Willi syndrome patients when treatment was started in early childhood (8).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts are undertaken to use the balloons in various disease entities related to obesity [6][7][8]. Similarly to other medical tests, the balloon insertions can also be followed by complications.…”
Section: Discussionmentioning
confidence: 99%
“…We also agree with the concept that obesity should be primarily prevented and treated with supervised reduced-energy diets, restricted access to food, and daily exercise regimen [2].When pharmacological, dietary, and behavioral approaches fail, however, to control body weight and obesity is progressive and severe (body mass index (BMI) over 40)-as occurs in patients not followed since birth or those referred when the obesity is already severe-the use of Bioenterics Intragastric Balloon (BIB) may represent an alternative and effective treatment for body weight control [3].In our study [4], younger patients appeared to benefit from treatment more than their older peers, and in the two youngest patients treated more than once, a substantial BMI reduction was maintained during a treatment period of 3 years. In one patient (12.4 years), we were able to maintain a satisfactory BMI control until the age of 17, when he underwent a successful biliopancreatic diversion.…”
mentioning
confidence: 91%